Long-Term Effect of Fertilizers and Amendments on Depth-Wise Distribution of Available NPK, Micronutrient Cations, Productivity, and NPK Uptake by Maize-Wheat System in an Acid Alfisol of NorthWestern Himalayas. Issue 18 (11th October 2017) - , Rajneesh; Sharma, R. P.; Sankhyan, N. K.; Kumar, Rameshwar
ABSTRACT: The present study was undertaken in the ongoing long-term fertilizer experiment initiated during 1972 at experimental farm of Department of Soil Science, Himachal Pradesh Agricultural University, Palampur (India). Soil samples collected from three depths (0–0.15, 0.15–0.30, and 0.30–0.45 m) were analyzed for pH; organic carbon; CEC; available N, P, and K; and micronutrients cations. Continuous use of optimal dose of fertilizers and FYM-influenced pH, organic carbon, CEC, available NPK, and DTPA extractable micronutrient cations significantly. The contents of organic carbon, available N, P, K, Fe, Mn, Zn, and Cu were higher in top soil layer (0–0.15 m) compared to lower depths (0.15–0.30 and 0.30–0.45 m). Highest productivity of wheat (89.89 q ha −1 ) and maize (156.52 q ha −1 ) was recorded under 100% NPK + FYM, which was at par with 100% NPK + lime. Application of 100% NPK along with amendments (FYM/lime) recorded significantly higher NPK uptake over other treatments.